2014
DOI: 10.1021/am500773g
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Catalytic Efficiency: A Function of Bio–Nano Interface Reactions

Abstract: Biocatalyst immobilization onto carbon-based nanosupports has been implemented in a variety of applications ranging from biosensing to biotransformation and from decontamination to energy storage. However, retaining enzyme functionality at carbon-based nanosupports was challenged by the non-specific attachment of the enzyme as well as by the enzyme-enzyme interactions at this interface shown to lead to loss of enzyme activity. Herein, we present a systematic study of the interplay reactions that take place upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
92
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 75 publications
2
92
0
1
Order By: Relevance
“…NP morphology can play a key role in impacting enzymatic enhancement as well. Since NPs/nanotubes maintain higher radii of curvature due to their smaller diameters, these materials allow for increased center-tocenter distances between adjacent immobilized enzymes while limiting unfavorable protein-to-protein interactions [28]. Furthermore, enzyme orientation can be controlled by careful manipulation of the enzyme attachment chemistry, allowing for strategic orientation of the substrate binding pocket of the immobilized enzyme away from the NP surface and toward incident substrate [29 ].…”
Section: Introductionmentioning
confidence: 99%
“…NP morphology can play a key role in impacting enzymatic enhancement as well. Since NPs/nanotubes maintain higher radii of curvature due to their smaller diameters, these materials allow for increased center-tocenter distances between adjacent immobilized enzymes while limiting unfavorable protein-to-protein interactions [28]. Furthermore, enzyme orientation can be controlled by careful manipulation of the enzyme attachment chemistry, allowing for strategic orientation of the substrate binding pocket of the immobilized enzyme away from the NP surface and toward incident substrate [29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immobilization onto nanosupports such as nanotubular aluminosilicate (71), graphene oxide (72), carbon nanotubes (73)(74)(75), graphene oxide sheets (74), nanodiamonds (76), and metal-oxide particles (77), was achieved either through physical or chemical means or through encapsulation into a gel (78) or membrane (79,80). Optimization of the immobilization conditions at any of these nanosupport interfaces involved controlling the enzyme interactions with the nanosupport or encapsulator (with or without a linker) (74) to preserve its functionality and catalytic behavior.…”
Section: Enzymes For Wastewater Treatmentmentioning
confidence: 99%
“…Optimization of the immobilization conditions at any of these nanosupport interfaces involved controlling the enzyme interactions with the nanosupport or encapsulator (with or without a linker) (74) to preserve its functionality and catalytic behavior. Typically, the immobilization interfaces could lead to non-specific interactions with the enzymes that could change its structure and conformation and decrease its catalytic activity (74). Previous studies have shown that additionally, protein-protein interactions (74,81) at such nanosupport interfaces could also lead to enzyme loss of activity (82).…”
Section: Enzymes For Wastewater Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…[11,12] Specifically, studies aiming to improve TiO2 reactivity under visible light irradiation proposed introducing suitable heteroatoms onto its structure [13,14] and/or narrowing its band-gap. [15] However, such heteroatoms inserts need special technologies processing (e.g., sputtering, [16] ion implantation, [17] thermal treatments, [18] and others), are high energy cost and largely inefficient when yield is desired, thus with limited large-scale consumer and industrial implementation. Further, photocatalysis efficiency of the heteroatoms modified semiconductor materials may not be significantly improved when compared to their starting counterpart.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%